Protective Role and Enhanced Intracellular Uptake of Curcumin in Retinal Cells Using Self-Emulsifying Drug Delivery Systems (SNEDDS) - Elide Zingale; Sebastiano Masuzzo; Tatu Lajunen; Mika Reinisalo; Jarkko Rautio; Valeria Consoli; Agata Grazia D’Amico; Luca Vanella; Rosario Pignatello (Pharmaceuticals)
Background: Sirtuin-1 (SIRT1), a histone deacetylase enzyme expressed in ocular tissues with intracellular localization, plays a critical protective role against various degenerative ocular diseases. The link between reduced SIRT1 levels and diabetic retinopathy (DR) has prompted the exploration of natural therapeutic compounds that act as SIRT1 agonists. Curcumin (CUR), which has been shown to upregulate SIRT1 expression, is one such promising compound. However, effective delivery of CUR to the deeper ocular tissues, particularly the retina, remains a challenge due to its poor solubility and limited ocular penetration following topical administration. Within this context, the development of self-nanoemulsifying drug delivery systems (SNEDDS) for CUR topical ocular delivery represents a novel approach. Methods: In accordance with our prior research, optimized SNEDDS loaded with CUR were developed and characterized post-reconstitution with simulated tear fluid (STF) at a 1:10 ratio, showing suitable physicochemical and technological parameters for ocular delivery. Results: An entrapment efficiency (EE%) of approximately 99% and an absence of drug precipitation were noticed upon resuspension with STF. CUR-SNEDDS resulted in a better stability and release profile than free CUR under simulated ocular conditions. In vitro analysis of mucoadhesive properties revealed that CUR-SNEDDS, modified with a cationic lipid, demonstrated enhanced interactions with mucin, indicating the potential for improved ocular retention. Cytotoxicity tests demonstrated that CUR-SNEDDS did not affect the viability of human corneal epithelial (HCE) cells up to concentrations of 3 μM and displayed superior antioxidant activity compared to free CUR in an oxidative stress model using retinal pigment epithelial (ARPE-19) cells exposed to hydroquinone (HQ). Cell uptake studies confirmed an enhanced accumulation of CUR within the retinal cells following exposure to CUR-SNEDDS compared to neat CUR. CUR-SNEDDS, at lower concentrations, were found to effectively induce SIRT1 expression. Conclusions: The cytocompatibility, antioxidant properties, and enhanced cellular uptake suggest that these developed systems hold promise as formulations for the delivery of CUR to the retina.